2010
DOI: 10.1212/wnl.0b013e3181ff96dd
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement in neurology: AAN Parkinson disease quality measures

Abstract: Background: Measuring the quality of health care is a fundamental step toward improving health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 23 publications
1
54
0
Order By: Relevance
“…2 The American Academy of Neurology (AAN) quality improvement guidelines recommend that neuropsychiatric symptoms should be assessed annually in all patients with PD. 3 When neuropsychiatric symptoms are observed, it is important to attempt to uncover the cause of these symptoms as they may be situational, medication related, the result of other medical conditions, intrinsic to PD or a combination of these factors.…”
Section: Supportmentioning
confidence: 99%
“…2 The American Academy of Neurology (AAN) quality improvement guidelines recommend that neuropsychiatric symptoms should be assessed annually in all patients with PD. 3 When neuropsychiatric symptoms are observed, it is important to attempt to uncover the cause of these symptoms as they may be situational, medication related, the result of other medical conditions, intrinsic to PD or a combination of these factors.…”
Section: Supportmentioning
confidence: 99%
“…It is doubtful, for example, that many primary care physicians are aware of or follow clinical guidelines for PD care published by the American Academy of Neurology. 32 Studies suggest that neurologist care in the management of PD improves outcomes. Using Medicare data to identify patients with PD, we found that only 40% of prevalent PD patients saw a neurologist over a 4-year period.…”
Section: Approaches To Maximize Functionmentioning
confidence: 99%
“…We describe our methodology in previous publications. 14 from the AAN guideline subcommittees to perform systematic reviews of the literature and to identify efficacious processes of neurologic care. Yet it is also clear that QMR and the AAN need to better inform AAN members about PQRS and other similar quality measurement programs.…”
mentioning
confidence: 99%